Core and critical cities of global region airport networks - Lordan, Oriol; Sallan, Jose M. (Physica A, 2019)
Air transport is one of the key infrastructures of today’s global economy. Connections between airports define airport networks, where nodes are cities served by airports, connected by edges if there is at least one direct flight connecting them. The aims of this research are to relate structural properties of airport networks which explain how these networks respond to isolation of critical nodes, and to gain insight into relevant socio-economic factors that influence the development of airport networks. We split the world airport network (WAN) into seven global region airport networks (GRANs), using the divisions established by OAG database. We gather information about structural properties of each GRAN determining core cities through k-core decomposition, and critical cities through robustness analysis. We find that differences of robustness across GRANs can be explained by the fraction of core cities relative to total cities. Furthermore, analysis of multilevel structure reveal relevant differences between GRANs, rooted on geographical and socio-economic factors, and give insight about how network robustness in airport networks can be enhanced. •This research relates structural determinants of regional airport networks robustness.•World airport network is divided into seven regions defined in OAG dataset.•We define core cities as the ones of the main core of k-core decomposition.•Critical cities are obtained through node selection criteria in robustness analysis.•Robustness of regional airport networks depends of the size of each main core.